(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Artificial Intelligence (AI) and Big Data Analytics have emerged as transformative technologies in modern healthcare, significantly improving diagnostic accuracy and enabling personalized treatment approaches. By leveraging large volumes of diverse medical data, including electronic health records, imaging, genomics, and patient-generated data, AI algorithms can detect complex patterns and predict disease outcomes more efficiently than traditional methods. This paper explores the integration of AI and Big Data tools in clinical decision-making processes, highlighting their applications in early diagnosis, risk stratification, and treatment customization. Furthermore, the study examines challenges such as data privacy, ethical concerns, and the need for interdisciplinary collaboration. Overall, the implementation of AI and Big Data analytics holds great promise for enhancing patient outcomes, optimizing healthcare resources, and advancing precision medicine.